An accurate and fast computational algorithm based on hybrid methods - al-Khazraji, Muhammad Thamir Kamil; Rashid, Muhammad; Shihab, Suha Naim; Rashid, Taha (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2021)
The numerical solutions of nonlinear equation for a single diode equivalent circuit of a solar cell are introduced. Four numerically algorithms, which include newton's; Predictor-Corrector Hally and Accelerated Predictor-Corrector Hally methods are described and compared in the present work. These algorithms are applied to calculate the voltage; current; power of a solar cell with the different values of load resistance programmed by Matlab language. The results showed that the proposed algorithm is the most efficient compare with other three algorithms.